2019
DOI: 10.3390/polym11050810
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Small-Diameter Vascular Graft Reinforced with a Braided Fiber Strut with Improved Mechanical Properties

Abstract: Acute thrombosis remains the main limitation of small-diameter vascular grafts (inner diameter <6 mm) for bridging and bypassing of small arteries defects and occlusion. The use of hydrogel tubes represents a promising strategy. However, their low mechanical strength and high swelling tendency may limit their further application. In the present study, a hydrogel vascular graft of Ca alginate/polyacrylamide reinforced with a braided fiber strut was designed and fabricated with the assistance of a customized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In addition, gelatin has been shown to have good biodegradability, biocompatibility, and has high cell/tissue affinity, which allows efficient tissue integration between scaffolds and native bone [ 12 ]. Hydrogels made from gelatin have a 3D macromolecular network that has a high-water content [ 13 , 14 ]. This characteristic not only enhances biocompatibility, it adds elasticity to hydrogels and thus makes it possible to better mimic native ECM [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gelatin has been shown to have good biodegradability, biocompatibility, and has high cell/tissue affinity, which allows efficient tissue integration between scaffolds and native bone [ 12 ]. Hydrogels made from gelatin have a 3D macromolecular network that has a high-water content [ 13 , 14 ]. This characteristic not only enhances biocompatibility, it adds elasticity to hydrogels and thus makes it possible to better mimic native ECM [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the HVGs and the RHVGs, a 3D casting mold was utilized. 26 Compared to the HVGs, the RHVGs contained a braided stent in the wall.…”
Section: Preparation Of the Hydrogel Vascular Grafts And The Braided mentioning
confidence: 99%
“…However, it was reported that the wall of the grafts was more prone to pseudoaneurysm and it has little longitudinal elasticity, thus restricting seeding of endothelial cells [6,7]. Therefore, the aim of this study was to develop artificial vascular grafts with structures similar to native blood vessels with the final goal of achieving regenerative medicine and organ reconstruction standards [8,9].…”
Section: Introductionmentioning
confidence: 99%